2023
DOI: 10.15561/26649837.2023.0607
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wrestlers at the Olympic Games: gender aspect

David Curby,
Milorad Dokmanac,
Fikrat Kerimov
et al.

Abstract: Background and Study Aim. With the increasing popularity of freestyle wrestling, the scientific community is paying more attention to gender factors that may influence the performance and success of competitive activities. The aim of study to determine differences in performance indicators between male and female wrestlers in the Olympic Games 2021. Material and Methods. The study included 192 athletes, consisting of 96 male wrestlers and 96 female wrestlers. An analysis of match records and video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
1
0
3
Order By: Relevance
“…This coincides with the results of previous years, which were obtained based on the analysis of the 2017 World Championship [32]. Some previous studies [33] were focused on factors that negatively affect spectacle. Our study showed that interruptions in matches (Challenge, Negative Wrestling, Caution) can be considered an indirect indicator of reduced spectacle in sports wrestling.…”
Section: Discussionsupporting
confidence: 90%
“…This coincides with the results of previous years, which were obtained based on the analysis of the 2017 World Championship [32]. Some previous studies [33] were focused on factors that negatively affect spectacle. Our study showed that interruptions in matches (Challenge, Negative Wrestling, Caution) can be considered an indirect indicator of reduced spectacle in sports wrestling.…”
Section: Discussionsupporting
confidence: 90%
“…Наявність емансипації сучасного спорту характеризується бурхливим розвитком швидкісно-силових видів спорту та єдиноборств з участю жінок (Тропін, та ін., 2022;Alsarve, & Tjønndal, 2020;Castan-Vicente, & Bohuon, 2020; (Голоха, & Тропін, 2023;Curby, and et. al., 2023;Porrovecchio, 2015; .…”
Section: вступunclassified
“…al., 2017) (Korobeynikov, et. al., 2018) Curby, D., Dokmanac, M., Kerimov, F., Tropin, Y., Latyshev, M., Bezkorovainyi, D., & Korobeynikov, G. (2023). Performance of wrestlers at the Olympic Games: gender aspect.…”
Section: вступmentioning
confidence: 99%
“…Сучасна боротьба характеризується зростанням напруженості та щільності змагальних поєдинків. Це пов'язано із зміною правил змагань та намагання Об'єднаного світу боротьби (UWW) зробити змагання більш видовищними (Curby, et. al., 2023).…”
Section: особливості психічного стану у кваліфікованих борцівunclassified